Analisis Butir Soal Elemen Membaca Dalam Buku Teks Bahasa Indonesia SMP Kelas VIII Berdasarkan Higher Order Thinking Skills (HOTS) - Kirana, Dewi; Nazurty, Nazurty; Saputra, Ade Bayu (Jurnal Ilmiah Dikdaya, 2024)
This research aims to describe the use of the Higher Order Thinking Skills (HOTS) cognitive category in the questions contained in the Indonesian language textbook for Class VIII Middle Schools published by the Ministry of Education and Culture of the Republic of Indonesia, Independent Curriculum 2021 Edition. This research uses qualitative research methods. The type of research used is content analysis. This research is also called analytical research, where the study is based on document analysis. The data for this research were taken from the HOTS type reading element questions found in the Indonesian Middle School Class VIII textbook published by the Ministry of Education and Culture in 2021. Based on the research results, it can be concluded that there are 51 questions in the Class VIII Indonesian Middle School textbook published by the Ministry of Education and Culture, Merdeka Curriculum In 2021, spread over 6 CHAPTERS, the lesson topics are HOTS (Higher Order Thinking Skills). These practice questions have the same question characteristics and are included in the cognitive categories C4 (analyzing), C5 (evaluating), and C6 (creating). These questions are included in the realm of KKO (Operational Verbs) level 3 (reasoning). The suggestions that can be put forward from this research are that textbook writers are advised to make efforts to improve the characteristics of HOTS C4, C5 and C6 questions based on Learning Objectives (TP) and other researchers are advised to research other aspects of HOTS.